Hollywood and anti-semitism : a cultural history up to World War II - Carr, Steven Alan, 1964- (Cambridge studies in the history of mass communications., 2001)
"Hollywood and Anti-Semitism: A Cultural History up to World War II examines how the public perceived American Jews in the entertainment industry from the turn of the century to the outbreak of World War II. Eastern European Jewish immigrants are often credited with building a film industry during the first decade of the twentieth century and dominating it by the 1920s. In this study, Steven Carr reconceptualizes Jewish participation in Hollywood by examining prevalent attitudes toward Jews among American audiences. Analogous to the Jewish Question of the nineteenth century, which was concerned with the full participation of Jews within the sphere of public life, the Hollywood Question of the twenties, thirties, and forties addressed the Jewish population within mass media. This study reveals the powerful set of assumptions about ethnicity and media influence as it related to the role of the Jew in the motion picture industry."--Jacket